2020
DOI: 10.3390/ijms21165930
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Intrinsically Disordered Regions of hnRNP-A2 and TDP-43 Accelerate TDP-43′s Conformational Transition

Abstract: Most biological functions involve protein–protein interactions. Our understanding of these interactions is based mainly on those of structured proteins, because encounters between intrinsically disordered proteins (IDPs) or proteins with intrinsically disordered regions (IDRs) are much less studied, regardless of the fact that more than half eukaryotic proteins contain IDRs. RNA-binding proteins (RBPs) are a large family whose members almost all have IDRs in addition to RNA binding domains. These IDRs, having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The hydrophobicity values were calculated using the ProtScale software [102] and parameters provided by Abraham and Leo, 1987 [103]. The C-terminal domain (Figure 2) is glycine-rich and mainly disordered [104], and several ALS-related mutations are located there [100]. The N-terminal domain (Figure 2) contains six beta-strands and one alpha helix [105] and is followed by two tandem RNA recognition motifs-RRM1 and RRM2, collectively referred to as RRM1/2-that are highly conserved and important for binding nucleic acids [28,106].…”
Section: The Tdp-43 Protein and Its Aggregationmentioning
confidence: 99%
“…The hydrophobicity values were calculated using the ProtScale software [102] and parameters provided by Abraham and Leo, 1987 [103]. The C-terminal domain (Figure 2) is glycine-rich and mainly disordered [104], and several ALS-related mutations are located there [100]. The N-terminal domain (Figure 2) contains six beta-strands and one alpha helix [105] and is followed by two tandem RNA recognition motifs-RRM1 and RRM2, collectively referred to as RRM1/2-that are highly conserved and important for binding nucleic acids [28,106].…”
Section: The Tdp-43 Protein and Its Aggregationmentioning
confidence: 99%
“…Subsequent studies confirmed that hyperphosphorylated TDP-43 impairs small interfering RNA silencing, which is the major post-transcriptional mechanism of retrotransposable elements or genomic parasites as a novel mechanism of neurodegeneration in ALS [14]. TDP-43 has been shown to contain a prion-like domain that can form a self-replicating amyloid conformation [15] TDP-43 possesses intrinsically disordered domains whereby the rate αhelix-to-β-sheet transition is dependent upon post translational modifications of phosphorylationdephosphorylation pathways [16]. Furthermore, prion-like domains may directly originate during viral genomic RNA processing involving nucleocapsid (NC) proteins responsible for virus capsid assembly and structure [17].…”
Section: Tdp-43 Hyperphosphorylation In Alsmentioning
confidence: 94%
“…Notably, while studying the interaction between HnRNP-A2 and TDP-43, a mechanism of reciprocal regulation through IDRs was evidenced: in some neurodegenerative diseases (see Section 4 ), TDP-43 shows a transition from an alfa-helix to a beta-sheet structure, which favors its aggregation, and it was found that an increase in the disordered conformation of HnRNP-A2 is directly related to the increase in the beta-sheet structure in TDP-43 [ 154 ]. Such a kind of interaction, based on IDRs, is probably responsible for the aggregation-dependent alterations noticed in most neurodegenerative diseases.…”
Section: Post-transcriptional Regulation Of Gene Expression In the Ne...mentioning
confidence: 99%